Oral-Facial-Digital Syndrome in an Indian Child - Sumedha Ballal; Sanjanaa Srinivasa; Mary Augustine (Indian Journal of Paediatric Dermatology)
Oral-facial-digital syndromes (OFDSs) are a rare heterogeneous group of genetic disorders characterized by a spectrum of craniofacial, oral, and digital anomalies. A 3-month-old female patient presented with facial milia, cleft lip and palate, nodule over the tongue, and syndactyly of digits and was diagnosed with OFDS type 1, a subtype of the syndrome, based on distinctive oral, facial, and digital features. This case report adds to our understanding of this rare condition and emphasizes the significance of the dermatologist’s and oral clinician’s roles in the multidisciplinary approach needed for early diagnosis, treatment, and follow-up in OFDS cases.